2013
DOI: 10.1002/cssc.201200800
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Hydrazinidoborane: A Chemical Hydrogen‐Storage Material

Abstract: Herein, we present the successful synthesis and full characterization (by (11) B magic-angle-spinning nuclear magnetic resonance spectroscopy, infrared spectroscopy, powder X-ray diffraction) of sodium hydrazinidoborane (NaN2 H3 BH3 , with a hydrogen content of 8.85 wt %), a new material for chemical hydrogen storage. Using lab-prepared pure hydrazine borane (N2 H4 BH3 ) and commercial sodium hydride as precursors, sodium hydrazinidoborane was synthesized by ball-milling at low temperature (-30 °C) under an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 46 publications
18
52
0
Order By: Relevance
“…The diffraction patterns were successfully indexed in the monoclinic phase with the space group P2 1 /n ( Figure S16). The unit cell parameters extracted at 81 K are reported in Table 1, and are in agreement with the literature [21]. Like for LiHB, the unit cell parameters of NaHB exhibit a positive evolution (Figure 10) and the unit cell volume presents a normal evolution with positive coefficient of thermal expansion ( Figure S17).…”
Section: Sodium Hydrazinidoborane Nahbsupporting
confidence: 84%
See 2 more Smart Citations
“…The diffraction patterns were successfully indexed in the monoclinic phase with the space group P2 1 /n ( Figure S16). The unit cell parameters extracted at 81 K are reported in Table 1, and are in agreement with the literature [21]. Like for LiHB, the unit cell parameters of NaHB exhibit a positive evolution (Figure 10) and the unit cell volume presents a normal evolution with positive coefficient of thermal expansion ( Figure S17).…”
Section: Sodium Hydrazinidoborane Nahbsupporting
confidence: 84%
“…With NaHB, the sodium cation is surrounded by five symmetry-equivalent anions [4,21]. The bigger size of Na + (116 pm vs. 90 pm for Li + ) explains its higher coordination degree and the bigger unit cell volume of NaHB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they suggested that the initial step would be characterized by the formation of dimers like NH2NH(M)BH2-NHNH(M)BH3 and NH2NH(M)BH=NNH(M)BH3 (with M as Li, Na or K) obtained by intermolecular reactions between H δ+ in one molecule and H δ− in another one. This is in agreement with the hypotheses reported by Moury et al [66,68]. Also, Chua et al [74] highlighted a clear correlation between the cation size and dehydrogenation properties of the metal hydrazinidoborane.…”
Section: Chemical Modification Of Hydrazine Boranesupporting
confidence: 82%
“…It is generally admitted that the dehydrogenation of boranes is complex [71], and the reference [72] is further evidence of such complexity. Moury et al [68] investigated the sodium derivative. Sodium hydride NaH showed high reactivity towards hydrazine borane.…”
Section: Chemical Modification Of Hydrazine Boranementioning
confidence: 99%